2015
DOI: 10.1007/s12311-015-0707-3
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Cerebellum in Cue-Dependent Force Changes During an Isometric Precision Grip Task

Abstract: The “raspberry task” represents a precision grip task that requires continuous adjustment of grip forces and pull forces. During this task, subjects use a specialised grip rod and have to increase the pull force linearly while the rod is locked. The positions of the fingers are unrestrained and freely selectable. From the finger positions and the geometry of the grip rod, a physical lever was derived which is a comprehensive measurement of the subject’s grip behaviour. In this study, the involvement of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…For example, in precision finger tasks such as the raspberry task [36,37], half of the young participants showed a conditioned change in force at just the second presentation of the conditioning stimulus [35] and personal observation of DFK. In contrast, cerebellar patients were significantly worse than control subjects at learning the necessary association [34]. For a successful association between the conditioned stimulus and the motor action, participants needed a well-planned and controlled execution of the task [35]; in cerebellar patients, this execution was impaired [25].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, in precision finger tasks such as the raspberry task [36,37], half of the young participants showed a conditioned change in force at just the second presentation of the conditioning stimulus [35] and personal observation of DFK. In contrast, cerebellar patients were significantly worse than control subjects at learning the necessary association [34]. For a successful association between the conditioned stimulus and the motor action, participants needed a well-planned and controlled execution of the task [35]; in cerebellar patients, this execution was impaired [25].…”
Section: Discussionmentioning
confidence: 89%
“…The cerebellum is known to be generally important for coordinating motor performance, such as diadochokinesis, and it is additionally important for associating sensory information with movements as well as for adapting movements [33]. Some studies have highlighted the cerebellum's importance in the context of participants' associative learning of grip forces [34,35]. For example, in precision finger tasks such as the raspberry task [36,37], half of the young participants showed a conditioned change in force at just the second presentation of the conditioning stimulus [35] and personal observation of DFK.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the two tasks differ in their use of arm/hand muscles, with a greater emphasis on finger muscles in tapping. Considering the different innervation of cortical and sub-cortical areas of the arms and fingers 42 , the individual variations in task performance may indicate different impairments of brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…As the axis of the thumb and index finger lies above the center of gravity of the object, it is to be expected that torques will arise that have to be compensated. It has been shown that the adaptation of the grip in the first moments of grip formation is very suitable to compensate for unwanted torques [ 4 , 5 , 34 ]. In particular, young healthy subjects, as they correspond to our participants, are very fast and efficient in this adaptation performance ([ 5 ], Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, young healthy subjects, as they correspond to our participants, are very fast and efficient in this adaptation performance ([ 5 ], Figure 2). In contrast, patients with cerebellar damage show significant limitations in adaptation ([ 34 ], Figure 5), which indicates the involvement of the cerebellum in the action. The cerebellum is involved in the coordination of multi-joint movements of the shoulder, arm, or finger joints [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%